ANALISIS KECAKAPAN HIDUP SISWA PADA PEMBELAJARAN EKONOMI KREATIF MELALUI PEMBELAJARAN BERBASIS PROYEK DI SMA NEGERI 15 PALEMBANG - Rafika Rahmadani; Riswan Jaenudin; Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
Formulation of the problem in this researh is how the values of the specific skills of students learning the creative economy through project based learning can see values on specific skills of students. The variables of this study are life skills that are restricted to specific skills and focused on values. the subject were SMAN 15 Palembang X. IPS 2 grade students and one teacherof the creative economy. observational data used to determine the values of the specific skills of the students, a quetionnaire used to determine students respons to learning the creative economy and the interview is used to determine the creative economy concept of learning through projrct based learning. the result showed that the values of the specific skills students consisting of academy pretty good. Result for the value of academic skill was 68,7% in the category is quite good and the value of vocational skills is 69,7% and can be quite good. It shows that with in the students have the values of the good life skills so that these values can be used as the procces of formation student skill.